Comparative Analysis of Time to All-cause Treatment Discontinuation and Rehospitalization among Early-phase Schizophrenia Patients Discharged on Long-acting Injectable Antipsychotics versus Oral Antipsychotics - Ta-Chun Lin; Ching-Hua Lin; Huei-Ping Chiu (Taiwanese Journal of Psychiatry)
Objectives: The early phase of schizophrenia is crucial in determining the long-term prognosis for patients with schizophrenia. In this study, we intended to compare time to all-cause discontinuation and rehospitalization within one year for early-phase schizophrenia patients discharged on long-acting injectable antipsychotics (LAIs) versus oral antipsychotics (OAPs). Methods: We analyzed data of early-phase schizophrenia patients, defined as having a duration of illness of at least six months and no more than seven years, discharged on either LAIs or OAPs from a psychiatric hospital in southern Taiwan between 2006 and 2021. Survival analysis was used to compare the time to all-cause discontinuation and rehospitalization within one year of discharge between LAIs and OAPs. With the temporal trend test and Cochran–Armitage trend test, we analyzed patients using LAIs, at discharge within the study period. Results: We included 2,301 patients for analysis. The LAIs group (n = 355) had a significantly longer time to all-cause discontinuation (p < 0.05) and a significantly longer time to rehospitalization (p < 0.01) than the OAPs group (n = 1,946). Patients with LAI use at discharge significantly demonstrated a significant increase from the first period to the last period (Z = 6.555, p < 0.001). Among patients discharged on LAIs, the prescription rate of second-generation antipsychotic LAIs was significantly increased over time (Z = 10.430, p < 0.001). Conclusion: For early-phase schizophrenia, LAIs were superior to OAPs in lengthening the time to all-cause discontinuation and rehospitalization. LAIs may be considered to prescribe initially, rather than being reserved solely for patients experiencing multiple relapses or displaying nonadherence to OAPs.